Improvement of Organization Management Performing Arts Ludruk Irama Budaya Sinar Nusantara - I.G.A Aju Nitya Dharmani (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Ludruk has a socio-cultural role for the people of East Java in the effort to preserve and develop the local culture. Especially as performing arts, ludruk can act as entertainment that can be enjoyed by various layers of society in East Java, the purpose of this study is: Describe the Improvement of the Management of the Organization of Performing Arts Ludruk Irama Sinar Nusantara Culture. Design/methodology/approach: This research is a qualitative sociological phenomenological study, based on the literature review. The data in this study form qualitative data consisting of three types, namely data behavior, oral data, and writing data. Instruments in this study are researchers themselves. Data analysis in this research consists of several activities that are done jointly, according to Miles and Huberman data reduction, display data and conclusion drawing / verification. Findings: The results of this study are: 1) In general in the approach of critical theorists of art and entertainment ludruk is the idea that they deserve attention for three reasons. First, the contents of art and works present a potentially revealing story of the human, social, and world way of working in the same way as the myth that offers a mimetic representation of the world of life experience. Secondly, ludruk as a means of art and entertainment produced reflects something from the way people live with real conditions is significant. Third, ludruk as an art, if not entertainment how able to entertain the fans as they start to switch to other entertainment. 2) Changes in the paradigm of technical managers in management skills so that the focus to practice the skills required to successfully manage ludruk seriously from various circles to preserve and develop it, to build maximum functional relationships with internal and external clients, it must have a management infusion by adopting the model most recently covering the organizational structure, the function of the marketing channel for the performing arts will lead to the improvement of the delivery of performing arts through more effective inter-organizational management, or certain services to predetermined consumption points, and more importantly improved performance is a change organizations in which managers and organizations that organize organizations place and manage programs that measure the current level of organizational performance and then generate ideas to modify organizational behavior and infrastructure incorporated into the temp at to achieve higher results. Originality/value: This paper is original Paper type: a Research Paper